Errors In Writing Educational Research For Master's And Doctoral Degrees In The Specialization Of Arabic Language Curriculum And Instruction In Egypt/ الأخطاء في كتابة البحوث التربوية في الماجستير والدكتوراه تخصص المناهج وطرق تدريس اللغة العربية في مصر - Abdulrahman Mohsen Hassan (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
Adhering to scientific methodology and sound scientific writing rules is a fundamental requirement when writing Master's theses and Doctoral dissertations. However, the recurrence of errors often limits the quality and utility of such research. This study focused on educational research within the specialization of Curriculum and Instruction of Arabic Language. It aimed to elevate the standard of such research by identifying common errors, presenting authentic examples, and guiding researchers on how to avoid them. The study employed a descriptive method, utilizing qualitative content analysis supplemented by descriptive statistics to determine error frequencies. It analyzed a comprehensive census of all 30 Master's theses and Doctoral dissertations submitted to the Department of Curriculum and Instruction of Arabic Language at a Faculty of Education in Egypt during the last three years, from 2023 to 2025. Thus, the sample represented the entire research population during that period. For analysis purposes, a content analysis checklist was developed, and its validity and reliability were verified. Results revealed 64 types of methodological and linguistic errors across 20 research elements, including the problem statement, terminology, and language. Prominent errors included formulating a nonresearchable question, citing secondary sources in defining terms, and errors in writing hamzat al-wasl and hamzat al-qat' (Arabic orthography). The study proposed corrective models for these errors. It recommended adding language courses to graduate programs, especially related to academic language, and providing applied training in scientific writing. It also proposed developing a list of scientific research standards based on the identified errors to guide future evaluative studies.